Insect/Bt-cotton interactions: Are immunological variables and hemocyte ultrastructure in Podisus nigrispinus (Hemiptera: Pentatomidae) affected? - Cunha, Franklin Magliano; Wanderley-Teixeira, Valéria; Teixeira, Álvaro Aguiar Coelho; Santos, Fábio André Brayner dos; Alves, Luiz Carlos; Caetano, Flávio Henrique [UNESP] (Taylor & Francis, 2013)
Recent studies have shown that ingestion by the army worm Spodoptera frugiperda of Cry1Ac toxin from Bt cotton promotes histochemical and ultrastructural changes in the digestive cells of the predatory pentatomid bug Podisus nigrispinus. Therefore, mindful of the changes in the midgut of the predator, which represents the first line of defence in this insect, our aim was to test the hypothesis that the consumption of Bt cotton-fed S. frugiperda by P. nigrispinus might lead to alterations in components of the immune system of P. nigrispinus. The Cry1Ac toxin level in the leaves of Bt cotton, nitric oxide, phenoloxidase activity, and total proteins were quantified by ELISA. Total and differential hemocyte counts were evaluated, and hemocyte ultrastructure analysis was undertaken. We found that ingestion of the prey fed daily with approximately 23 ± 0.70 ng g-1 Cry1Ac by wet weight of leaves, and expressed by the Bt cotton, induces small ultrastructural changes in the predator's granulocytes and plasmatocytes. However, these changes did not affect the total number and differential and humoral variables analyzed for the bug's hemocytes. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Bacillus thuringiensis; immunity; morphology; predator; ultrastructure; annelid; bacterium; cotton; immune system; insect; nitric oxide; protein; toxin